Respuesta :

r3t40

We have a function,

[tex]f(x)=x^2-1[/tex]

and we are asked to find its inverse function.

An inverse function essentially gets you the original value that was dropped into a function.

For example,

If I put 5 into [tex]f(x)[/tex] I will get 24. Now If I take 24 and put it into the inverse function I have to get number 5 back.

The way to determine the inverse function swap the x and the [tex]f(x)[/tex], then solve for [tex]f(x)[/tex],

[tex]x=f(x)^2-1[/tex]

[tex]f(x)^2=x+1[/tex]

[tex]f(x)=\pm\sqrt{x+1}[/tex]

Of course the notation demands that the obtained function be called,

[tex]f^{-1}(x)=\pm\sqrt{x+1}[/tex]

Hope this helps :)